A partial least square structural equation modelling preliminary analysis on total quality management elements and environmental regulation and policy influencing organisational performance in the food and beverage companies of Malaysia - Akanmu, Muslim Diekola; Bahaudin, Ahmad Yusni; Jamaludin, Roslan (Inderscience Enterprises Ltd., 2017)
There have been inconsistent findings in the literature concerning the relationships between TQM and organisational performance. Quality assurance and continuous process improvement as TQM elements and organisational performance considered in this study are moderated by environmental regulation and policy (ERP). The objective of this study is threefold: to propose an inclusive research model comprising the antecedent factors proposed in the model to improve organisational performance in the Malaysian food and beverage companies; to serve as validation process for the developed instruments of the ongoing research with the identified constructs of the study; and to show the preliminary analysis and the results. Data were collected from 35 respondents using a 55-items instrument. PLS SEM measurements model was used to assess the reliability and validity of the instruments in this study. The result shows that the instruments are reliable and the pilot study indicates a strong evidence of rational validity.